2021
DOI: 10.1007/jhep06(2021)061
|View full text |Cite
|
Sign up to set email alerts
|

Universal statistics of vortices in a newborn holographic superconductor: beyond the Kibble-Zurek mechanism

Abstract: Traversing a continuous phase transition at a finite rate leads to the breakdown of adiabatic dynamics and the formation of topological defects, as predicted by the celebrated Kibble-Zurek mechanism (KZM). We investigate universal signatures beyond the KZM, by characterizing the distribution of vortices generated in a thermal quench leading to the formation of a holographic superconductor. The full counting statistics of vortices is described by a binomial distribution, in which the mean value is dictated by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…Indeed, a framework to account for the distribution of topological defects generated across a classical continuous phase transition has been put forward and predicts a binomial distribution, in agreement with numerical simulations for the timedependent Ginzburg-Landau theory [45]. In higher dimensional systems, further evidence for the presence of universality in the full counting statistics of topological defects has been provided by the study of the vortex number distribution in a newborn holographic superconductor, which was predicted to be Poissonian [46]. At the time of writing, experimental evidence of Poissonian vortex statistics has been reported after cooling of an atomic Bose gas into a superfluid in finite time [47].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Indeed, a framework to account for the distribution of topological defects generated across a classical continuous phase transition has been put forward and predicts a binomial distribution, in agreement with numerical simulations for the timedependent Ginzburg-Landau theory [45]. In higher dimensional systems, further evidence for the presence of universality in the full counting statistics of topological defects has been provided by the study of the vortex number distribution in a newborn holographic superconductor, which was predicted to be Poissonian [46]. At the time of writing, experimental evidence of Poissonian vortex statistics has been reported after cooling of an atomic Bose gas into a superfluid in finite time [47].…”
Section: Introductionmentioning
confidence: 61%
“…A growing body of results [41][42][43][44][45][46] suggests that the signatures of universality govern the kink number distribution and not only its mean value. To appreciate this, in a classical setting, it suffices to assume that the formation of kinks at different locations is described by independent stochastic events [45].…”
Section: Beyond the Kibble-zurek Mechanism: Kink Number Statisticsmentioning
confidence: 99%
“…These results have also been extended to nonlinear quenches [17,18] and inhomogeneous systems [19][20][21][22][23], while their breakdown has been characterized in open systems [24][25][26]. More recently, it has been shown that signatures of universality are present in the full kink-number distribution and that all cumulants scale as a universal power-law of the quench time [16,[27][28][29][30][31]. The universal dynamics of defect formation is not always desirable, and a variety of works have been devoted to circumvent it using diverse control protocols [32][33][34][35][36][37][38][39][40][41][42], beyond the use of nonlinear quenches and inhomogeneous driving.…”
Section: Introductionmentioning
confidence: 85%
“…These results have also been extended to nonlinear quenches [16,17] and inhomogeneous systems [18][19][20][21][22], while their breakdown has been characterized in open systems [23][24][25]. More recently, it has been shown that signatures of universality are present in the full kink-number distribution and that all cumulants scale as a universal power-law of the quench time [15,[26][27][28][29][30]. The universal dynamics of defect formation is not always desirable, and a variety of works have been devoted to circumvent it using diverse control protocols [31][32][33][34][35][36][37][38][39][40][41], beyond the use of nonlinear quenches and inhomogeneous driving.…”
Section: Introductionmentioning
confidence: 85%